Análise da viabilidade econômica e ambiental de um sistema solar fotovoltaico no complexo turístico serrote do jatobá de Pau dos Ferros-RN - Gonçalves, Gustavo Leite (Universidade Federal Rural do Semi-Árido, 2019)
This work comprises the elaboration and analysis of a grid-connected photovoltaic system project for the Serrote do Jatobá Tourist Complex, followed by an assessment of the environmental and economic feasibility through the discounted pay-back and check list methods, respectively. The research is justified by the need to diversify the national energy matrix, recurrent from the oil crisis and intense implementation of sustainability in civil construction. It covers a description, design and design of an electric energy generation system directed to a tourist complex in Pau dos Ferros-RN, enumerating the environmental aspects and identifying the positive aspects in magnitude and comprehensiveness when compared to negatives, as well as analysis of the return of cash flow in future, removing the investment around the 4th and 5th year of operation, which is done for the rest of the useful life.
Keywords: Semiárido; Energia solar; Fontes alternativas de energia; Complexo Turístico Serrote do Jatobá; Semi-arid; Solar energy; Alternative energy sources; Serrote do Jatobá tourist complex; ENGENHARIAS::ENGENHARIA SANITARIA